How much day surgery? Delphic predictions. Issue 6658 (12th November 1988) - Gabbay, J.; Francis, L.
Abstract : A list was compiled of 83 of the commonest operations, which according to published reports may be performed on day patients but which in our district were usually performed on inpatients. The results of a national Delphi study among anaesthetists and general surgeons who were known to be in favour of day surgery produced estimates of the probable rates of day surgery for each of those operations under ideal conditions. Comparison of these figures with those from a Delphi study carried out in one district and with figures for day surgery carried out in that district and with waiting list figures enabled two health districts to focus their efforts to increase day surgery. The figures from the national Delphi study could be applied in other districts if the following are taken into account: Hospital Activity Analysis data must be validated; though there was consensus among the national Delphi consultants, personal clinical opinions varied; the case load may grow as waiting lists decrease.